A highly permeable hollow fibre substrate for Pd/Al2O3 composite membranes in hydrogen permeation. (2nd March 2015) - Gouveia Gil, Ana; Reis, Miria Hespanhol M.; Chadwick, David; Wu, Zhentao; Li, K.
Abstract In this study, a highly permeable ceramic hollow fibre substrate has been fabricated for developing Pd composite membranes. The substrate consists of one thin outer sponge-like layer for depositing Pd membranes by electroless plating and a plurality of self-organized micro-channels for reducing gas permeation resistance. A dense defect-free Pd membrane with approximately 1 μm was formed on the outer surface of the sponge-like layer, which suggests a great uniformity of the substrate. As a result, a hydrogen permeation flux of 0.87 mol s−1 m−2 can be achieved at 450 °C and 165 KPa. Hydrogen permeation of the several composite membranes with different Pd thicknesses (1.0 and 3.3 μm) and different substrates sintered at different temperatures (1300 and 1400 °C) was also investigated. It was found that an intermediate layer, which is normally formed due to the Pd penetration during the electroless plating, shows an adverse effect in hydrogen permeation, especially when the Pd membrane is very thin.